Directivity of Self-Fulfillment and Personal Realization of Teenager - Golovanova N.F; Dermanova I.B (Moscow State University of Psychology and Education, 2018)
The authors ground the necessity to clarify the terminological and phenomenological specifics of the terms: "self-fulfillment", "personal development", "self-development". The attention is drawn to the formal usage of these terms in the pedagogical science and the ambiguous interpretations by different scientific schools of psychology. The research of the manifestation of self-fulfillment and personal development is performed based on a selection of 126 teenagers, engaging the "Personal growth" scales from the methods of psychological well-being by C. Ryff, the "Personal growth" scales from the methods of "Life aspirations" by E.Deci, R.Ryan, as well as the author's method of directivity to self-fulfillment and method to reveal the significance by V.Y, Kotlyakov. For the first time the authors' questionnaire to measure the self-development in different life spheres is employed. The analysis of the empirical results allows to make a grounded statement that the contemporary teenagers have a prevailing egocentric directivity of self-fulfillment and reveals as well the importance of the interest to the moral aspects of being and the interiorized values of personal growth for the harmonious self-fulfillment of the teenager.